128 DO PARENTS GIVE IBUPROFEN OR ACETAMINOPHEN TO CHILDREN PRIOR TO EMERGENCY DEPARTMENT VISITS FOR FEVER OR PAIN?. (1st January 2005) - McCain, J. E.; Monroe, K. W.; King, W. D.; Freeman, C.
Abstract : Purpose of Study: Most nonemergent visits to the emergency department (ED) include fever or pain in the chief complaint. This study was designed to examine the use of ibuprofen and acetaminophen for fever and/or pain prior to ED visits, highlighting patients who were given no medications prior to the visit and noting whether parents would have brought their children to the ED if fever or pain had resolved with medication. Methods: This is a convenience sample of children > 8 weeks old presenting to a Children's Hospital ED with complaints of fever and/or pain. Our goal was to capture nonemergent patients; patients were excluded if referred by a pediatrician, were immunocompromised, or arrived by EMS. One investigator administered a questionnaire to all participants. Data were entered into Epistat® for statistical analysis. Results: Between 6/04 and 8/04, we enrolled 116 patients: 51% female, 51% African-American, 46% Caucasian, and 2% Hispanic. Of all study patients, 51% were insured by Medicaid, 29% had private insurance, and 20% had no insurance. 66% had a private pediatrician, 27% went to health departments, and 7% had no primary pediatrician. Mean patient age was 4.8 (SD 4.9) and mean parental age was 31.2 (SD 10.6). The mother completed the questionnaire in 69% of cases. Parental education varied between 6th grade and postgraduate degrees. Chief complaint included fever in 51% and pain in 84%. Mean length of time with fever was 2.7 days (SD 3.6 d) and mean length of time with pain was 3.6 days (SD 4.8 d). Caregivers gave no medications for pain or fever in 23% of patients (95% CI 15.9, 32). Acetaminophen was given to 44% of patients prior to ED visit and 48% had received ibuprofen prior to ED visit. Of those patients who received ibuprofen and/or acetaminophen, 63% were given appropriate doses, 36% were given too little, and 4% were given too much. 54% of parents reported that if pain or fever had resolved with medication, they would not have brought their children to the ED. Conclusion: Many parents give ibuprofen or acetaminophen prior to ED visits for pain and fever (77%), but only 2/3 of parents give appropriate doses of these medications. About one-half of parents reported that they would not have brought their children to the ED if pain or fever had resolved at home. Parents should be counseled on appropriate dosing as well as appropriate use of ibuprofen and acetaminophen at home when children have pain or fever.